Markers of receptivity-resistance of origin somatoform disorders in young people - Leshchyna Ірина; Mozgova Тетяна (Psychosomatic Medicine and General Practice, 2018)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the markers of receptivity-resistance of origin somatoform disorders in young people